2022
DOI: 10.1115/1.4056238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Purge Flow Injection on the Performance of an Axial Turbine With Three-Dimensional Airfoils and Non-Axisymmetric Endwall Contouring

Abstract: In this paper, we present the evaluation of the aerodynamic robustness to rim seal purge flow of an optimized 1.5-stage axial turbine configuration with a bowed stator profile and endwall contouring. Performance maps obtained by experiments and numerical simulations show that the efficiency benefit gained by this optimized configuration is partially reduced by the injection of purge flow through the cavity downstream of the first stator. Measurements with five-hole probes and hot-wire probes, as well as unstea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In order to investigate the behaviour of the design by Poehler et al (2015) (hereinafter referred to as "F3D configuration"), a secondary air system was integrated into the axial turbine test rig at the IST and detailed measurements of the efficiency and local flow conditions in the rig were carried out. The results of this measurement campaign can be found in Schäflein et al (2022). Together with numerical simulations, these experiments demonstrated that the F3D configuration loses parts of its efficiency gains when purge flow is injected.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…In order to investigate the behaviour of the design by Poehler et al (2015) (hereinafter referred to as "F3D configuration"), a secondary air system was integrated into the axial turbine test rig at the IST and detailed measurements of the efficiency and local flow conditions in the rig were carried out. The results of this measurement campaign can be found in Schäflein et al (2022). Together with numerical simulations, these experiments demonstrated that the F3D configuration loses parts of its efficiency gains when purge flow is injected.…”
Section: Introductionmentioning
confidence: 79%
“…In a previous paper on this project (Schäflein et al, 2022), it had already been demonstrated that the purge flow has virtually no effect on the flow inside the stator passages. It was also shown that the numerical simulations are able to reproduce the local flow measurements downstream of the rotor (MP2) with good accuracy.…”
Section: Numerical Validationmentioning
confidence: 92%
See 2 more Smart Citations